Glycerol and galactose substituted zinc phthalocyanines. Synthesis and photodynamic activity - Zorlu, Yunus; Ermeydan, Mahmut Ali; Dumoulin, Fabienne; Ahsen, Vefa; Savoie, Huguette; Boyle, Ross W. (Springernature, 2009)
Three novel water soluble, non-ionic, zinc phthalocyanines (Pcs) have been synthesized and their spectroscopic and photodynamic properties investigated in aqueous media. One of the three compounds was shown to be significantly less aggregated, when compared to the other two compounds, and this effect was found to be related to both the nature of the substituent, and also the position at which it is attached to the macrocycle. Photodynamic activity and cellular uptake by human adenocarcinoma cells (HT-29) was shown to be linked to the aggregation state of the Pcs in water.
Keywords: In-Vitro; Behavior